The Influence of Race/Ethnicity on Disparities in Correctional Dispositions: Examining How Risk Assessment & Neighborhood Socioeconomic Context Affects Sentencing Decisions of Adjudicated Juveniles, Ohio, 2010-2016 - Campbell, Christina A. ([Verlag nicht ermittelbar], 2024)
The overall goal of this research project was to examine the impact that risk assessment has on the sentencing of racial minority youth and youth from disadvantaged neighborhoods. One of the main goals of correctional risk assessment is to reduce disparate outcomes for certain groups of youth in the juvenile justice system (e.g. Black youth). In practice, risk assessment is used with this goal in mind. However, there is very little research which shows whether or not risk assessment actually has its intended effects on sentencing. Therefore, this study set out to examine whether or not risk assessment reduces the sentencing gap seen in most research for minority youth and youth from disadvantaged neighborhoods. In addition, several other important research topics were explored to understand the role that race and socioeconomic disadvantage play in the juvenile justice system. These research topics included: (1) variation in the predictive validity of risk assessment across race, (2) variation in the predictive validity of risk assessment across neighborhood disadvantage, and (3) the moderating effects of race/gender and court dispositions on the predictive validity of risk assessment. To achieve the research goals in this study, data was collected from a large juvenile court in a Midwestern County. Information from 4,383 youth that came into contact with the court between January 2010 and December 2016 were included in the study. Data was collected that related to youth demographics, neighborhood characteristics in which youth lived, risk assessments data measured by the Ohio Youth Assessment System (OYAS), treatment programming received, court dispositions/sentencing, and recidivism.